(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Historical thinking skills have become the mantra of the history profession. The aims, objectives and outcomes of history classes and courses at both secondary and tertiary level resonate with the inclusion of the skills of the historian’s craft. Primary materials are among the tools included in school teaching packs and university readers to inculcate the research dimension of history coupled to analysis, selection, critical thinking, and logical formulation. In this article we propose to reflect on a recently developed component of a postgraduate Honours module introduced in the Department of Historical and Heritage Studies at the University of Pretoria in collaboration with the University archive. This element involved students engaging with un-inventorised virgin primary documentation emanating from the Museum of the Transvaal Education Department. They were tasked with not only having to critically read the content of the “box”, but to sort, appraise and contextualize the documentation. In addition, the brief also required students to consider the research potential of the contents and present their findings at a colloquium entitled “What’s in the Box?” We argue that the success of this component of the course took the students one step further in the making of history and thus exposed them to experiential learning and what could be termed the “inner workings” of the historians’ craft.